Інтродукція рослин Stevia rebaudiana (Bert.) Bertoni в Національному ботанічному саду ім. М.М. Гришка НАН України - Rakhmetov, D.B.; Levchyk, N.Ya.; Shpak, L.M.; Hrakhov, V.P.; Boiko, O.M.; Lyubinska, A.V.; Rakhmetova, S.O.; Zavhorodniy, V.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2016)
The results of long-term studies of Stevia rebaudiana (Bert.) Bertoni are presented, viz. plant morphology parameters, propagation, cultivation, constituents. Stevia is characterized by significant food and medicinal properties and is promising introduced species in Ukraine. In M.M. Gryshko National Botanical Garden the valuable gene pool is accumulated which has numbered more than 20 forms. The nutritional media and environment needs for introduction to the culture in vitro and long-term storage of plant and also their regeneration from leaf explants. The content of antioxidants (flavonoids and ascorbic acid) in stevia raw material has been evaluated. The leaves of Stevia rebaudiana have been accumulated the diterpeneglycosides up to approximately 6–7 % (to dry weight). This is dynamic indicator that depends on Stevia form and cultivation conditions. Maximal accumulation of steviosides was observed in open ground plants in budding-bloo ming phases. Stevia rebaudiana plants regardless of the form and the cultivation conditions (open and protected ground, in vitro) are characterized by low levels of drought tolerance. Plants growing in open ground conditions demonstrate higher drought tolerance compared with plants in vitro. The biggest water-retaining capacity, both in soil and in vitro conditions, is found in form R100, the lowest – in form 3T.